The humanistic approach to boost self-confidence in English as a foreign language EFL students’ oral skills. - Moscoso Erazo, Ana Sofía (2025)
This research examines how the Humanistic Approach in teaching English as a foreign language (EFL) influences students' self-confidence in communicating orally. Through a qualitative study based on one-on-one interviews, the perceptions and experiences of teachers applying this approach in their classrooms were explored. The findings reveal that the Humanistic Approach fosters an emotionally supportive environment, where empathy, open communication, and constructive feedback are essential for enhancing students' self-confidence. Teachers emphasized that normalizing mistakes, celebrating achievements, and offering individualized support are key strategies for addressing frustration and insecurity among students. Moreover, they observed positive changes in students' attitudes, such as increased motivation, social and academic growth, and a greater willingness to face challenges. The methodologies used include Total Physical Response (TPR), Suggestopedia, and collaborative work, all designed to create a safe space that prioritizes emotional well-being and personal growth. The main challenges reported involved addressing the diversity of personalities and learning levels, which were overcome through effective communication, emotional support, and the creation of a trusting environment. In conclusion, the Humanistic Approach not only strengthens students' self-confidence in oral communication but also improves classroom dynamics, fostering a more holistic, empathetic, and student-centered learning experience.